A ortografia nos livros didáticos do 6º e 7º anos do Ensino Fundamental - Ana Luiza de Souza Couto (2020)
The difficulty of teaching and learning spelling is the reality in the rooms of Brazilian public schools. Bearing in mind that the textbook acts as an ally of the teacher in the classroom, the analysis of how the spelling approach in textbooks is relevant. In view of this, this research aimed to reflect on the spelling approach of the sixth and seventh years textbooks approved in the PNLD 2017. As specific objectives, this research sought to: identify the spelling in educational documents, os Parâmetros Curriculares Nacionais [National Curricular Parameters] (PCNs), Programa Nacional do Livro Didático [National Textbook Program] (PNLD), Base Nacional Comum Curricular [National Curricular Common Base] (BNCC); analyze the spelling contents of books; evaluate how the teacher's manual guides the teacher about working with spelling. The theoretical framework of the research is the Integration of Multiple Patterns (IMP), theory, postulated by Treiman and Kessler (2014), in addition to the studies by Treiman (2017) and Treiman (2018), who argue that the learning of spelling should occur by multiple patterns, always considering the relationship between spelling and meaning. Linked to these works, the studies by Morais (2010) and Soares (2018) were used, which reflect on the regular and irregular relations of Portuguese spelling. The methodology used are a qualitative and quantitative analysis of the orthographic content and the description of the official educational documents (PCNs, PNLD and BNCC). As a result, the research identified that the educational documents address spelling in general, but don’t point to more specific paths for practice, nor the treatment with specific difficulties. In relation to textbooks, there are collections that carry out reflective work with spelling, with activities that motivate students to reflect on the orthographic aspects of Portuguese. On the other hand, there are collections that are still based on mechanical and transmissive teaching, where memorization is prioritized at the expense of understanding and generalizations. In addition, collections prioritize the development of orthographic irregularities and / or accentuation, instructions on contextual regularities and regularities are minimal. The work with spelling often outside the text and without prioritizing regularities and understanding the rules when they exist leads to a decrease in the student's role and his direct role as a knowledge builder.